2018
DOI: 10.1111/jocn.14315
|View full text |Cite
|
Sign up to set email alerts
|

What are they talking about? Content of the communication exchanges between nurses, patients and relatives in a department of medicine for older people—An ethnographic study

Abstract: Nurses can use the communication content to create conditions enabling them to obtain a holistic view of the patient's life history and to develop an appropriate person-centred care plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In this regard, Johnsson et al. (2018) pointed out that information exchanged among nurses, older adults, and family caregivers had to do primarily with the patient's health, test results, and medication. As it happens, hospitalized older adults are likely to present various comorbidities that can seriously complicate the care provided them (Marti, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Johnsson et al. (2018) pointed out that information exchanged among nurses, older adults, and family caregivers had to do primarily with the patient's health, test results, and medication. As it happens, hospitalized older adults are likely to present various comorbidities that can seriously complicate the care provided them (Marti, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The patients in our study reported a lack of information, lack of understanding or problems remembering oral and written information about nutrition. Johnsson, Wagman, Boman and Pennbrant [44] found that the information nurses most commonly provided to older patients was related to their routine work, such as disease symptoms, test responses and drug changes. The authors emphasised the importance of the communication content and the value of asking didactic questions to improve the patients' and relatives' understanding of the information and to increase patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…The first element of the ICN Code of Ethics for nurses––nurses and people––emphasized PCC in nursing care [ 13 ]. It focuses on nurses' interactions with people who access care in the healthcare setting and requires that nurses promote a conducive environment in which the human rights, values, customs, and spiritual beliefs of individuals, families, and communities are respected [ 13 , 29 , 30 ].…”
Section: Main Textmentioning
confidence: 99%